Comparative evaluation of posttraumatic stress symptoms and negative life outcomes in pregnant women with and without hyperemesis gravidarum - Haydeh Hashemizadeh; Roshanak Noori Dolooee (Mashhad University of Medical Sciences, 2017)
Introduction: Hyperemesis gravidarum is often accompanied by severe physical and mental stress. This type of vomiting can lead to complication and reducing the quality of life. This study was performed with aim to assess posttraumatic stress symptoms (PTSS) in pregnant women with and without Hyperemesis gravidarum. Methods: This case-control study was performed on 350 pregnant women with Hyperemesis gravidarum and 350 pregnant women without Hyperemesis gravidarum who referred to the clinics and hospitals of Taamin Ejtemaee of Mashhad in 2014-2015. Data was collected through interview with mothers and completing the standard questionnaires of IES15 , PTSS10 and evaluation of negative life outcomes. Data were analyzed by SPSS software (version 20) and independent t-test, Chi-square, Fisher's exact test and U Mann-Whitney test. P<0.05 was considered significant. Results: The mean PTSS scores in case and control groups were 138±4 and 28±3, respectively, that independent t-test showed that the difference was statistically significant (P <0.001). Also, significant difference was found between case and control groups in terms of negative life outcomes especially regarding financial issues, marital status, professional issues, as well as regarding psychological and physical well-being (P<0.05). Conclusion: Pregnant women with Hyperemesis gravidarum are at more risk for developing PTSS and negative life outcomes compared to healthy pregnant women, so management and control of these patients seems to be necessary.